Content Marketing as a Tourism Promotion Strategy: A Conceptual Review - Abashidze, Irakli (European Scientific Journal, ESJ, 2025)
The global tourism industry is characterized by a fluctuating and unpredictable market environment, where advanced marketing approaches are essential to gaining and maintaining competitiveness. Content marketing has emerged as a powerful strategy to promote tourism services in such conditions. Its potential in achieving various marketing objectives makes it one of the primary choices for managing communication with target audiences. As online technologies develop, modern trends emerge at the same pace. Adopting these trends and technologies ensures an effective influence on travelers’ behavior. Furthermore, to establish long-lasting and valuable relationships with customers, content marketing decisions must be data-driven. Thus, successful management of marketing communications in the tourism industry relies heavily on content creation, distribution across various channels, and the evaluation of its effectiveness. However, challenges related to measurement precision persist. To address these challenges in content marketing management within the tourism sector, it is essential to regularly examine the issue as it evolves both theoretically and in terms of practical application. The issue is multifaceted and requires complex research considering multiple factors. This paper reviews the concept from various perspectives to analyze the key aspects of modern content marketing management in tourism, which is the objective of the study. To achieve this, a contemporary literature review is conducted. The final section of the paper provides conclusive remarks and findings regarding the management of content marketing in the current conditions of the tourism industry and technological advancements.